A survey of multi-objective metaheuristics applied to structural optimization - Zavala, Gustavo R.; Nebro, Antonio J.; Luna, Francisco; Coello Coello, Carlos A. (Structural and multidisciplinary optimization, 2014)
In civil and industrial engineering, structural design optimization problems are usually characterized by the presence of multiple conflicting objectives, as to get the minimum investment cost and the maximum safety of the final design. This issue makes these problems to have not only one single solution, but a set them. Such solutions represent the possible trade-offs among the different objectives to be optimized. This paper reviews the latest developments in the field of multi-objective metaheuristics for solving design problems focusing on the optimization of the topology, shape, and sizing of civil engineering structures. We review both the algorithms and the applications, and the most relevant features of the solvers and the design optimization problems are analyzed. The paper ends by addressing a number of relevant and open issues that can be the subject of further research.